Community Involvement in Packaging Innovation Ensuring the Sustainability of Destination - Ni Luh Putu Agustini Karta; Ni Made Christine Dwiyanti; Ni Made Manik Prasanthi Bendesa; I Ketut Sutapa (International Journal of Social Science and Business, 2022)
During the Covid-19 Pandemic, many villas were closed, but many rural communities still needed to rebuild tourism. This study aimed to analyze local communities' involvement in packaging tourism villages in Cepaka and Petak villages during the Covid 19 pandemic to make them sustainable. This research is qualitative. Data and information are collected from stakeholders who are the primary sources. The informants were ten people in Petak village and 16 in Cepaka village. Focus group discussions (FGDs) were conducted in two villages, and in-depth interviews were conducted with all key informants using structured interview guidelines. The data analysis technique used is descriptive qualitative analysis. The findings of this study are spontaneous and induced community involvement in packaging the potential for village tourism and spiritual nature to provide economic, social, and environmental benefits. Developing tourist destinations that consider social, economic, and environmental values ​​​​has a balanced impact on society and business and ensures sustainability. Touches digital marketing creativity in packaging, improves product display quality, and accelerates information dissemination with unlimited coverage. The packaging of the Cepaka tourism village and the Petak spiritual nature tourism through synergy and collaboration with MSMEs and stakeholders enhances the destination's image.